Test and numerical simulation of anti-penetration mechanism for reinforced aluminum matrix SiC composites - JI Chen; LI Suyun (Zhongguo Jianchuan Yanjiu, 2018)
[Objectives] In order to study the anti-penetration failure mechanism of new lightweight composite armor plates, a graphene-reinforced aluminum-based SiC composite armor plate is proposed. [Methods] The microstructures of graphene reinforced aluminum matrix SiC composites are observed using light and scanning electron microscopy;combined with a ballistic gun test,a half model is established using AUTODYN finite element software,with a fragment mass of 30 g and a target plate thickness of 43 mm. Different constitutive models are used to describe the materials,and numerical simulation is carried out.[Results] Combining the ballistic gun test and simulation calculations,the anti-penetration process of the graphene reinforced aluminum-based SiC composite target is as follows:when the fragment penetrates the target plate,the aluminum alloy on the target plate is crushed by the fragment,forming a ring-shaped crimp break. During the backward extrusion process,the target plate is continuously eroded by the head,the fragments continue to impact the remaining target plate deformation cone and the fragment speed is great enough to form a petal-shaped breach through the target plate. [Conclusions] Combining microstructure observation and the ballistic gun test,the simulation results show that among the three constitutive models of Johnson-Cook, Cowper-Symonds and Johnson-Holmquist,the latter is more suitable for describing the anti-penetration mechanisms of graphene-reinforced aluminum-based SiC composites.